Pengaruh Variabel Makroekonomi terhadap Utang Luar Negeri di Negara ASEAN-7 - Abidin, Rafi Nur; Syahnur, Sofyan; Suriani, Suriani (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze the effect of macroeconomic variables (economic growth, exchange rates, and inflation) on foreign debt in ASEAN-7 countries (Indonesia, Thailand, Vietnam, Philippines, Laos, Cambodia, and Myanmar) during the period 1996 to 2019 which using the Autoregressive Distributed Lag (ARDL) panel model. The results show that foreign debt in ASEAN-7 is positively and significantly affected by economic growth, exchange rates, and inflation in the long term, but not in the short term. Therefore, ASEAN-7 countries are expected to pay attention to increasing foreign debt, overcome by pragmatic macroeconomic policies, especially policies regarding exchange rates and inflation.